Методика редагування фахових текстів студентами медичних вузів на заняттях з дисципліни "Українська мова (за професійним спрямуванням)" - Козиряцька, Світлана Анатоліївна; Козыряцкая, С. А.; Kozyryatska, S. (My University, 2014)
У статті розглянуто основні аспекти редагування фахових текстів студентами медичних вузів на заняттях з «Української мови (за професійним спрямуванням)» та запропоновано методику такого редагування. Приділено увагу правилам літературного слововживання та типовим стилістичним порушенням у текстах, наголошено на необхідності відпрацювання професійної лексики. В статье рассматриваются основные аспекты редактирования профессиональных текстов студентами медицинских вузов на занятиях по дисциплине “Украинский язык (профессиональное направление)” и предложена методика такого редактирования. Уделено внимание правилам литературного словоупотребления и типичным стилистическим нарушенияхі в текстах, отмечена необходимость отработки профессиональной лексики. Today’s society demands from the university graduates not only the high level of their professional knowledge and skills, but also general literacy of the future specialists. Hence, the modern graduates, including the graduates of medical institutes must not only correctly write and express their opinion, correctly conclude commercial papers, but also understand the main issues of language policy, lexical richness of their native language, morphological, syntactic and stylistic aspects, own standards of modern Ukrainian literary language, be able to hold a business conversation and more. The practice of higher medical educational institution requires productive techniques aimed at forming among the medical students the speech and language competence, culture of professional broadcasting. And one of the ways of its development is to work with professional texts, namely their translation and editing, as these types of work make it possible to expand the vocabulary of future professionals teach them consistently and convincingly to express their opinion, avoiding excessive information. This article is devoted to the study of fundamental aspects of professional editing of texts and the development of working method with it accordingly. Professional text editing includes not only good possession of terminology, but also the ability to provide clearly specific information of the narrow specialization. The article states that students should be given sufficient motivation, explaining on what are oriented exercises for professional editing of texts and that skills developed as a result of their implementation would be beneficial to them as future doctors; it is also must be explained that there are different types of errors; what kinds of edits can be applied (editing, correcting, editing shortcuts, processing). Attention is paid to the rules of literary usage and typical stylistic violation of texts, the need for practicing the professional vocabulary is stressed in the article.
Methods of professional editing of texts by medical students on the lessons of the «Ukrainian language (for professional purposes)»
Методика редактирования профессиональных текстов студентами медицинских вузов на занятиях по дисциплине “Украинский язык (профессиональное направление)”
Keywords: фахові тексти; медична термінологія; редагування; точність слововживання; помилки змісту; мовленнєві помилки; граматичні помилки; профессиональные тексты; медицинская терминология; редактирование; томность словоупотребления; ошибки содержания; речевые ошибки; грамматические ошибки; professional texts; medical terminology; editing; accuracy usage; content errors; speech errors; grammatical mistakes